2016
DOI: 10.1039/c5sm02464a
|View full text |Cite
|
Sign up to set email alerts
|

Anion triggered metallogels: demetalation and crystal growth inside the gel matrix and improvement in viscoelastic properties using Au-NPs

Abstract: Progelator complex Zn-TRPA-2 undergoes Cl(-) triggered gelation to afford ZTP2G, while Zn-TRPA-2 capped Au-NPs under similar conditions gave another gel GNZTP2G which also represents a rare nano-composite metallogel. When Zn-TRPA-2 was triggered by Cl(-) and NO3(-) simultaneously, crystals of demetalated species NA-TRPA-2 grew inside the ZTP2G matrix. Interestingly, GNZTP2G exhibits superior viscoelastic properties over ZTP2G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Moreover, a decrease in the negative gradient of complex viscosity (η*) also confirms the strengthening of the hydrogel after the incorporation of the antibiotic NFT (Figure 9b). 74,76 These results thus confirm the stable nature of the L3@NFT-doped gel. 91 It is noteworthy that the L3@NFT gel does not release the doped antibiotic if the gel is suspended in water for 24 h. Such a fact not only implies the efficient binding of NFT with L3 in the resultant gel network (cf.…”
Section: ■ Introductionsupporting
confidence: 75%
“…Moreover, a decrease in the negative gradient of complex viscosity (η*) also confirms the strengthening of the hydrogel after the incorporation of the antibiotic NFT (Figure 9b). 74,76 These results thus confirm the stable nature of the L3@NFT-doped gel. 91 It is noteworthy that the L3@NFT gel does not release the doped antibiotic if the gel is suspended in water for 24 h. Such a fact not only implies the efficient binding of NFT with L3 in the resultant gel network (cf.…”
Section: ■ Introductionsupporting
confidence: 75%
“…Contextually, the average dimension for ZTP2G fibers was reported to be ∼30 nm. 61 Further, fluorescence microscopy images suggested that the synthesized CLMG fibers along with ZTP2G are fluorescent in nature and emit brightly under blue, green, or red filters ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 96%
“…The average lifetime for ZTP2G has been calculated to be 2.93 ns. 61 Again, similar measurements have been made on luminogens L-1–L-3 exclusively, and thereafter, a comparative analysis has been performed to realize the interaction between the components in the hybrid systems (CLMGs). It has been found that τ av of L-1 (3.54 ns) is greater than those of L-2 (3.45 ns) and L-3 (2.76 ns) ( Figure S7 ), but all of these are much lower with respect to CLMGs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 In many instances, the presence of a particular cation or anion or a chemical substance influences the network structure in a great way to bring about significant changes in the associated properties. 27,28 This characteristic of a soft material to discriminate a particular entity from similar other motifs can endow special power to the material for enormous sensing capacity. There are several reports where LMWGs can sense different cations and anions in the gel state particularly with the help of a drastic change in the aggregateinduced emission property.…”
Section: ■ Introductionmentioning
confidence: 99%